2018
DOI: 10.1016/j.jecp.2018.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Automatic imitation effects are influenced by experience of synchronous action in children

Abstract: By their fourth year of life, children are expert imitators, but it is unclear how this ability develops. One approach suggests that certain types of experience might forge associations between the sensory and motor representations of an action that may facilitate imitation at a later time. Sensorimotor experience of this sort may occur when an infant's action is imitated by a caregiver or when socially synchronous action occurs. This learning approach, therefore, predicts that the strength of sensory-motor as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Recently, important steps have been taken to create tasks that can be used across multiple ages. For example, Van Schaik and Hunnius (2018) have developed a method for measuring nonconscious mimicry in children and Essa, Sebanz and Diesendruck (2019), as well as O'Sullivan, Bijvoet-van den Berg and Caldwell (2018), have measured automatic imitation in children. In a similar vein, McGuigan (2011) and Horowitz (2003) have measured imitative fidelity in explicit tasks with adults.…”
Section: How Can Social Imitation Be Measured?mentioning
confidence: 99%
“…Recently, important steps have been taken to create tasks that can be used across multiple ages. For example, Van Schaik and Hunnius (2018) have developed a method for measuring nonconscious mimicry in children and Essa, Sebanz and Diesendruck (2019), as well as O'Sullivan, Bijvoet-van den Berg and Caldwell (2018), have measured automatic imitation in children. In a similar vein, McGuigan (2011) and Horowitz (2003) have measured imitative fidelity in explicit tasks with adults.…”
Section: How Can Social Imitation Be Measured?mentioning
confidence: 99%
“…Altogether, sensorimotor simulation is a complex and poorly understood phenomenon that needs further exploration given its importance in social learning (e.g. Paulus et al, 2011;de Klerk et al, 2014;Rayson et al, 2017;O'Sullivan et al, 2018;de Klerk et al, 2019), interpersonal bonding (e.g. , body representations , social cognition (Meltzoff, 1990(Meltzoff, , 2007, and language processing (e.g.…”
Section: Embodied Simulation and Emotion Recognitionmentioning
confidence: 99%
“…Automatic imitation studies allow a more direct investigation of the neurocognitive mechanisms underlying imitation (i.e., the AON), negating the aforementioned confounds regarding motivation and cognitive strategy. While automatic imitation has been studied extensively in adults (see Cracco et al, 2018), to the best of our knowledge O'Sullivan et al (2018) were recently the first to study automatic imitation effects in children (aged 3-7 years), who were presumably free of neurodevelopmental disorders. Those authors found a significant automatic imitation effect in the movement initiation times for children within this age range, and also that these initiation times reduced with increased age.…”
Section: Introductionmentioning
confidence: 99%